G17-modified hammerhead ribozymes are active in vitro and in vivo - Kalweit, Anne (Cold Spring Harbor Laboratory Press, 2013)
Natural hammerhead ribozymes (HHRz) feature tertiary interactions between hairpin loops or bulges in two of three helices that surround the catalytic core of conserved nucleotides. Their conservation was originally established on minimal versions lacking the tertiary interactions. While those sequence requirements in general also apply to natural versions, we show here differences for the HHRz cleavage site N17. A guanosine at this position strongly impairs cleavage activity in minimal versions, whereas we observe for the G17 variants of four tertiary stabilized HHRz significant cleavage and ligation activity in vitro. Kinetic analyses of these variants revealed a reduced rate and extent of cleavage, compared with wild-type sequences, while variants with distorted tertiary interactions cleaved at a reduced rate, but to the same extent. Contrary to this, G17 variants exhibit similar in vitro ligation activity as compared with the respective wild-type motif. To also address the catalytic performance of these motifs in vivo, we have inserted HHRz cassettes in the lacZ gene and tested this β-galactosidase reporter in Dictyostelium discoideum. In colorimetric assays, we observe differences in the enzymatic activity of β-galactosidase, which correlate well with the activity of the different HHRz variants in vitro and which can be unambiguously attributed to ribozyme cleavage by primer extension analysis.